RSL3 induces ferroptosis by activating the NF-κB signalling pathway to enhance the chemosensitivity of triple-negative breast cancer cells to paclitaxel - Jialin Yuan; Cong Liu; Chengwei Jiang; Ning Liu; Zhaoying Yang; Hua Xing (Scientific Reports)
Abstract Chemotherapy resistance in triple-negative breast cancer (TNBC) leads to poor therapeutic effects and a poor prognosis. Given that paclitaxel-based chemotherapy is the main treatment method for TNBC, enhancing its chemosensitivity has been a research focus. Induced ferroptosis of tumour cells has been proven to increase chemosensitivity, but its ability to sensitize TNBC cells to paclitaxel (PTX) is unknown. In our experiments, measurements of viability and proliferation validated the synergistic effect of PTX combined with RSL3 on TNBC cells. The accumulation of intracellular Fe2+ and lipid reactive oxygen species, as well as the expression of malondialdehyde, illustrated that RSL3 enhanced the chemosensitivity of TNBC to PTX by inducing ferroptosis. Through transcriptome sequencing, a series of differentially expressed genes were identified, in which the expression of cytokines, such as CXCLs, was significantly increased in the treatment group, and the effect of combination therapy on TNBC was enriched mainly in the NFκB signalling pathway. In subsequent validation experiments, the use of the NF-κB inhibitor BAY11-7082 reversed the inhibitory effects of PTX and RSL3 on TNBC cell activity. In a xenograft immunodeficient mouse model, the inhibitory effects of PTX and RSL3 on TNBC in vivo were further verified. Our research validated the synergistic effects of PTX and RSL3 both in vivo and in vitro, with RSL3 inducing ferroptosis by activating the NF-κB signalling pathway, thereby increasing the chemosensitivity of TNBC to PTX. This study provides new insights for improving the therapeutic efficacy of treatment strategies.